Catalase-peroxidase StKatG2 from Salinicola tamaricis: a versatile Mn(II) oxidase that decolorizes malachite green - Ding, Mengyao; Wang, Wenjing; Lu, Zhenkun; Sun, Yuhui; Qiao, Xinzhen; Dai, Meixue; Zhao, Guoyan (Frontiers in Microbiology, 2024)
Manganese (Mn) oxidation processes have garnered significant attention recently due to their potential for degrading organic pollutants. These processes are primarily catalyzed by Mn(II) oxidases. Salinicola tamaricis F01, an endophytic bacterium derived from wetland plants, has demonstrated Mn(II)-oxidizing capacity. In this study, a catalase-peroxidase, StKatG2, was cloned and overexpressed in Escherichia coli from the strain F01. The purified recombinant StKatG2 exhibited Mn(II)-oxidizing activity with Km and Kcat values of 2.529 mmol/L and 2.82 min−1, respectively. Optimal catalytic conditions for StKatG2 were observed at pH 7.5 and 55°C, with 45.1% activity retention after an 8-h exposure to 80°C. The biogenic manganese oxides produced by StKatG2 exhibited mixed-valence states with Mn(II), including Mn(III), Mn(IV), and Mn(VII). Furthermore, StKatG2 demonstrated superior decolorization efficiency for malachite green (MG), achieving decolorization rates of 73.38% for 20 mg/L MG and 60.08% for 50 mg/L MG, while degrading MG into 4-(dimethylamino)benzophenone. Therefore, the catalase-peroxidase StKatG2 exhibits multifunctionality in Mn(II)-oxidizing activity and has the potential to serve as an environmentally friendly enzyme for MG removal.